Calorie adequacy for optimal cognitive recovery among traumatic brain injury patient - Noor Aini, Mohd Yusoff; Aryati, Ahmad; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Ahmad Zubaidi, A.latif (2017)
Cognitive recovery become a major concern to traumatic brain injury (TBI) patients and their caregivers because patients need to resume their normal life after hospital discharge. Recent discovery shows that calorie restriction is good for cognitive recovery, associated with low mortality rate and better clinical outcome. However adequate calorie needed for optimal cognitive recovery is not determined yet. This pilot study involved nine respondents recruited from Hospital Sultanah Nur Zahirah, Kuala Terengganu. The respondents underwent a series of nutritional assessment, neuropsychology test, and electroencephalography (EEG) for 3-5 days according to days of full calorie intake (CI) achieved based on their requirement. The demography, nutritional and neuropsychology data were analysed using SPSS with CI% set as independent variable and time to finish (FT) trail-making and total score (TS) of Montreal Cognitive Test set as dependent variable. EEG data was analysed using FFT and later power ratio was calculated by comparing slow to fast EEG band during first and subsequent visit. Preliminary result using scatter/dot graph showed relation of CI% to FT and TS at early part but plateau at certain range of CI% at later part. Pearson correlation test showed significant negative correlation between CI% to FT (r = -0.615; p = 0.000) and positive correlation to TS (r = 0.838; p = 0.000). Result also indicated that cognitive improved at low CI% and the mean different of power ratio for EEG of follow-up and first visit was significant (p = 0.03). In this pilot study, it appears that cognitive function shows improvement with calorie restriction.